2021
DOI: 10.1016/j.jconrel.2020.10.062
|View full text |Cite
|
Sign up to set email alerts
|

A thermoresponsive hydrogel system for long-acting corticosteroid delivery into the paranasal sinuses

Abstract: Delivering localized treatment to the paranasal sinuses for diseases such as chronic rhinosinusitis (CRS) is particularly challenging because of the small natural openings leading from the sinuses that can be further obstructed by presence of inflammation. As such, oral steroids, topical nasal sprays or irrigation, and surgery can be utilized to treat persistent sinonasal inflammation, but there exists a need for post-operative options for long-term steroid delivery to prevent disease recurrence. In the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 46 publications
(72 reference statements)
0
27
0
Order By: Relevance
“…The University of Pittsburgh Institutional Animal Care and Use Committee (IACUC) approved this study in eighteen 2-kg to 4-kg male and female New Zealand rabbits, which were evaluated for therapeutic intervention. 7 Inflammation of the left maxillary sinus was induced as described by Cho et al 2 Briefly, using a 1.9-mm 0-degree endoscope (Karl Storz, Tuttlingen, Germany) for visualization, partial Merocel (Medtronic, Minneapolis, MN) (∼12-mm × 3-mm × 1-mm) was placed to occlude the middle meatus of anesthetized rabbits (S.E.L. and E.W.W.).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The University of Pittsburgh Institutional Animal Care and Use Committee (IACUC) approved this study in eighteen 2-kg to 4-kg male and female New Zealand rabbits, which were evaluated for therapeutic intervention. 7 Inflammation of the left maxillary sinus was induced as described by Cho et al 2 Briefly, using a 1.9-mm 0-degree endoscope (Karl Storz, Tuttlingen, Germany) for visualization, partial Merocel (Medtronic, Minneapolis, MN) (∼12-mm × 3-mm × 1-mm) was placed to occlude the middle meatus of anesthetized rabbits (S.E.L. and E.W.W.).…”
Section: Methodsmentioning
confidence: 99%
“…At the study endpoint (4 weeks post-disease state), specimens were prepared for histopathology with hematoxylin and eosin (H&E) staining, as described. 7 Tissue sections were scored for epithelial cell damage, subepithelial edema, and inflammation of the submucosal glands from 0 to 3 (none, mild, moderate, or severe, respectively) and cilia damage from 0 to 2 (normal, disrupted, or loss). Scores for these 4 criteria were multiplied by a value representing the involvement across the maxillary sinus cross-section of 0 to 3 (none, up to one-third, one-third to two-thirds, or twothirds to diffuse).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously engineered a system called TEMPS (Thermogel, Extended‐release Microsphere‐based delivery to the Paranasal Sinuses) that consists of degradable poly(lactic‐ co ‐glycolic acid) microspheres (PLGA MSs) embedded in a nondegradable poly( N ‐isopropylacrylamide) (pNIPAAm)‐based thermoresponsive hydrogel. [ 10 ] This system is designed with a reversible liquid‐to‐gel transition near body temperature, which allows it to conform to the sinonasal mucosa and retain the controlled release microspheres in apposition to the tissue. Recently, we have shown that this delivery system can provide sustained release of a corticosteroid that, when applied to rabbit sinuses, reduced signs of inflammation.…”
Section: Introductionmentioning
confidence: 99%